Influence of Varying Plant Densities and Nitrogen Levels on Yield Attributes and Yield of Sweet Corn - Bhatt, P. Spandana; Yakadri, M.; Sivalakshmi, Y. (International Journal of Bio-resource and Stress Management, 2012)
A field experiment was conducted to study the effect of varying plant densities and nitrogen levels on yield attributes and yield of sweet corn during kharif 2009 at Agricultural Research Institute, ANGRAU, Rajendranagar, Hyderabad, India. In this investigation, three plant densities viz., P1-66,666, P2-80,000 and P3-1,00,000 plants ha-1 and four nitrogen doses i.e. N1-120, N2-160, N3-200 and N4-240 kg ha-1 were tested on sweet corn hybrid sugar -75. Out of all 12 combination of treatments, P2N4 (80,000 plants ha-1 with 240 kg N ha-1) was found to have performed significantly better in terms of yield attributes and yield.